Nano ZnO / red mud composite modifier made from solid waste and its preparation method and application
By preparing nano ZnO/red mud composite modifier, the nano ZnO is loaded onto the red mud by hydrolyzing precipitation method, and combined with acidification, ultrasonication and organicization treatment, the problem of uneven distribution of nano ZnO and red mud in asphalt is solved, and the efficient aging performance of asphalt and the service life of the pavement is improved.
Patent Information
- Application Number
- CN202411917348.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In the prior art, nano ZnO and red mud are unevenly distributed in asphalt, making it difficult to achieve coordinated efficiency and prone to agglomeration, which limits the ability to improve the aging performance of asphalt.
By preparing nano ZnO/red mud composite modifier, the nano ZnO is loaded onto the red mud by hydrolyzing precipitation method, combined with acidification and ultrasonic treatment, the specific surface area and dispersion uniformity of the red mud are improved, and then organic treatment is carried out to improve the compatibility of the composite modifier and asphalt.
The uniform dispersion of nano ZnO and red mud in asphalt is achieved, the agglomeration effect is reduced, the thermal oxygen aging and ultraviolet aging resistance of asphalt is improved, and the service life of asphalt pavement is extended.
Smart Images

Figure CN119350717B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of road materials, and specifically relates to a nano ZnO / red mud composite modifier made from solid waste, and a preparation method and application thereof. The present invention mainly focuses on nano composite materials and resource utilization of solid waste, and specifically relates to the innovative development of a new nano ZnO / red mud composite modifier made from solid waste and its application in road materials. Background Art
[0002] Asphalt pavement has been widely used due to its superior performance. However, asphalt will experience short-term aging during the paving and rolling process. In addition, asphalt pavement will experience serious long-term aging due to long-term exposure to the air, high temperature, oxygen and ultraviolet radiation during service, which will cause asphalt performance to decline and road diseases to occur easily, which will have a serious impact on the service life of the asphalt pavement.
[0003] As an industrial solid waste, red mud has a strong alkalinity that can cause serious pollution to soil and groundwater. How to recycle red mud is a problem that needs to be solved urgently. Studies have shown that adding red mud as a modifier to asphalt can improve the anti-rutting performance of asphalt. The surface of red mud has many gaps, so it has a large specific surface area, which can not only adsorb asphalt, but also slow down or inhibit the entry of oxygen, thereby improving the thermal oxygen aging resistance of asphalt. However, red mud will also agglomerate due to its large specific surface area. When added to asphalt as a modifier, there will be problems of uneven dispersion; nano ZnO, as a nano material, exhibits excellent performance in ultraviolet absorption and scattering, and can effectively improve the ultraviolet aging resistance of asphalt, but its resistance to thermal oxygen aging is relatively limited, and when it is added to asphalt as a modifier, the agglomeration effect is obvious, which causes a large defect in the modification effect.
[0004] Therefore, in order to take into account the modification effects of nano ZnO and red mud on asphalt and improve the asphalt's resistance to thermal oxidation aging and light oxidation aging, the two are physically blended and directly added to the molten asphalt for high-speed shearing and physical stirring. However, despite the high-speed shearing and physical stirring process, nano ZnO and red mud are still unevenly distributed in the asphalt, and are accompanied by agglomeration, making it difficult for the two to achieve a coordinated synergistic effect. Studies have shown that when unorganized nano ZnO is fused with red mud and asphalt, there are interface defects. This defect causes the low-temperature performance of the modified asphalt to decrease, limiting the ability to improve the aging performance of asphalt.
[0005] In summary, combining the advantages of solid waste resource utilization and nanomaterial performance, developing a new type of nano ZnO / red mud composite modifier made from solid waste will not only help solve the problem of solid waste treatment, but also further improve the anti-aging performance and pavement performance of asphalt materials, which has important environmental benefits and practical effects. However, there are few studies on the new type of nano ZnO / red mud composite modifier, and its preparation process needs further exploration. Summary of the invention
[0006] In view of the problem that after high-speed shearing and physical stirring processes are used in the prior art, nano ZnO and red mud are still unevenly distributed in asphalt, and agglomeration occurs, making it difficult for the two to achieve coordinated synergistic effects, the present invention provides a nano ZnO / red mud composite modifier made from solid waste and its preparation method and application. It can improve the anti-aging performance of asphalt in environments such as heat, oxygen, and ultraviolet light, extend the service life of asphalt pavement, and at the same time provide a new solid waste treatment solution to improve environmental benefits.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The first purpose of the present invention is to prepare a nano ZnO / red mud composite modifier.
[0009] A method for preparing a nano ZnO / red mud composite modifier made from solid waste comprises the following steps:
[0010] (1) The red mud recovered from the factory is crushed by a crusher, washed with deionized water, and then the obtained sample is filtered and dried to constant weight, followed by sieving to obtain purified and dried red mud;
[0011] The red mud is sintered red mud or Bayer red mud combined process red mud;
[0012] (2) dispersing the purified and dried red mud in step (1) in deionized water in a mass ratio of 1:4 between the purified and dried red mud and the deionized water, stirring to form a suspension, adding oxalic acid to the suspension in a mass ratio of 5:1 between the purified and dried red mud and the oxalic acid, and obtaining a mixed solution 1;
[0013] Then the obtained mixed solution 1 is placed in a constant temperature water bath and stirred evenly for 100 minutes, the speed is 600r / min, the temperature is set to 70°C, and the test pH is 6-8. After the reaction is completed, the obtained product is filtered, dried to constant weight, and finally ground and sieved to obtain acidified red mud;
[0014] (3) dissolving zinc salt in deionized water to form a zinc salt solution with a concentration of 0.3 mol / L; adding the acidified red mud obtained in step (2) and a surfactant to the zinc salt solution according to a ratio to obtain a mixed solution 2, wherein the ratio of zinc ions to acidified red mud is 60 mmol / g, and the molar ratio of zinc ions to surfactant is 1:6; subjecting the mixed solution 2 to ultrasonic treatment for 20 min at a frequency of 100 Hz, and then adding a precipitant to obtain a mixed solution 3, wherein the molar ratio of the precipitant to zinc ions is 3:1;
[0015] The zinc salt is zinc acetate, and is analytically pure;
[0016] The surfactant is anhydrous ethanol;
[0017] The precipitant is urea of analytical grade;
[0018] (4) The mixed solution 3 in step (3) was placed in a constant temperature water bath and stirred evenly for 2 h at a speed of 300 r / min and a temperature of 85° C. After the stirring was completed, the mixed solution was filtered and dried to a constant weight to obtain a red mud product loaded with nano-ZnO precursor;
[0019] (5) placing the red mud product loaded with nano ZnO precursor obtained in step (4) in a muffle furnace and calcining for 2 h at a temperature of 350° C., and finally grinding and sieving to obtain a red mud product loaded with nano ZnO;
[0020] (6) The red mud product loaded with nano-ZnO obtained in step (5) is dispersed in anhydrous ethanol, wherein the mass ratio of the red mud product loaded with nano-ZnO to the anhydrous ethanol is 1:5; an organic coupling agent is added, wherein the mass ratio of the red mud product loaded with nano-ZnO to the organic coupling agent is 12:1, and the organic coupling agent is an aluminate coupling agent or a titanate coupling agent; the mixture is stirred uniformly in a water bath for 2 hours at a speed of 360 r / min and a temperature of 85° C. After the reaction is completed, the mixture is filtered, dried to constant weight, and finally ground and sieved to obtain a nano-ZnO / red mud composite modifier made from solid waste; the nano-ZnO / red mud composite modifier made from solid waste has the following performance parameters:
[0021] ① It has a specific surface area of 23.574m2 / g and nano-scale pore size, a pore volume of 0.11cc / g, and an average pore size of 3.742nm;
[0022] ②Through XRF testing, the proportion of ZnO in the nano ZnO / red mud composite modifier is 61.6%-63.0%.
[0023] In the present invention:
[0024] Furthermore, in step (1), the red mud is washed with deionized water at a mass ratio of 1:8 between crushed red mud and deionized water; the red mud is preferably sintered red mud; the drying is preferably performed by placing the sample in a ventilated oven for drying at a temperature of 108°C; the filtration is preferably performed once; and the sieving is preferably performed with a sieve hole size of 300 mesh.
[0025] Furthermore, the filtration in step (2) is preferably performed three times; the drying is preferably performed in a ventilated oven at a drying temperature of 108° C.; and the sieving is preferably performed with a sieve size of 300 mesh.
[0026] Furthermore, the number of filtrations in step (4) is preferably one time; and the drying is preferably carried out in a ventilated oven at a drying temperature of 60°C.
[0027] Furthermore, the sieving in step (5) preferably has a sieve size of 300 mesh.
[0028] Furthermore, in the drying step (6), the sample is preferably placed in a ventilated oven for drying at a temperature of 60° C.; and in the sieving step, the sieve size is preferably 300 mesh.
[0029] The second object of the present invention is to provide a nano ZnO / red mud composite modifier made from solid waste, which is obtained by using the above-mentioned preparation method of a nano ZnO / red mud composite modifier made from solid waste. The nano ZnO / red mud composite modifier made from solid waste has the following performance parameters:
[0030] ①With 23.574m 2 / g specific surface area and nanoscale pore size, pore volume of 0.11cc / g, and average pore size of 3.742nm;
[0031] ②Through XRF testing, the proportion of ZnO in the nano ZnO / red mud composite modifier is 61.6%-63.0%.
[0032] The present invention provides a new method for solid waste treatment, prepares a single nano ZnO modifier, a single red mud modifier, a nano ZnO + red mud compound modifier and a nano ZnO / red mud composite modifier, and verifies that the nano ZnO / red mud composite modifier has the best performance.
[0033] The third object of the present invention is to provide an application of the above-mentioned nano ZnO / red mud composite modifier made from solid waste, which is used to prepare ZnO / red mud composite modified asphalt, delay the aging effect of asphalt, and extend the service life of the road surface.
[0034] A method for preparing nano ZnO / red mud composite modified asphalt comprises the following steps:
[0035] (1) Prepare the following raw materials in the following mass proportions: 100 parts by mass of modified asphalt, including 95 parts by mass of 70# road petroleum asphalt and 5 parts by mass of nano ZnO / red mud composite modifier;
[0036] (2) After heating 95 parts by weight of asphalt to a molten state at 150°C, 5 parts by weight of the nano ZnO / red mud composite modifier was added thereto. After preliminary stirring, the asphalt was placed in an oil bath and sheared at 3000 r / min for 1 h using a high-speed shearing machine. Then, the asphalt was stirred at 2000 r / min for 1 h using a mechanical stirrer to ensure that the modifier prepared above was evenly dispersed in the asphalt. Finally, the nano ZnO / red mud composite modified asphalt was obtained. The prepared nano ZnO / red mud composite modified asphalt had the following performance parameters: viscosity of 559.4 Pa at 135°C, softening point of 49.9°C, softening point of 51.8 dmm at 25°C, and elongation of 562 mm at 15°C.
[0037] Furthermore, the 70# road petroleum asphalt described in step (1) has a softening point of 47.6°C, a needle penetration of 64dmm-65dmm measured at 2°C, and an elongation of more than 1500mm measured at 15°C.
[0038] The reaction principle of the present invention is as follows:
[0039] (1) First, the red mud mixture is acidified with oxalic acid; then the Zn is released by the ionization process of the zinc salt solution. 2+ , as a source of zinc; the ionized Zn 2+ It is attached to the red mud through van der Waals force and cation exchange effect; then, a precipitant is added and heat treated to promote the Zn 2+ The nano-ZnO is fixed on the red mud in the form of a basic carbonate compound; thereafter, the nucleation and evolution process of the zinc oxide nanocrystals is carried out by a calcination process while being attached to the red mud, so as to strengthen the bonding strength between the nano-ZnO and the red mud; then, an aluminate coupling agent is used for organic treatment, so that the composite modifier is transformed from hydrophilic to lipophilic, and the compatibility of the composite modifier with asphalt is improved, and finally a new type of nano-ZnO / red mud composite modifier is obtained; finally, the composite modifier treated as above is mixed with asphalt by a melt blending method to prepare a modified asphalt product;
[0040] (2) Specific reaction process:
[0041] ① Acidification treatment:
[0042] HOOC-COOH+2OH - =C2O42- +2H2O
[0043] ② Urea hydrolysis:
[0044] Urea hydrolysis at high temperature provides an alkaline environment:
[0045] CO(NH2)2+H2O→NH4 + + OH - +CO3 2-
[0046] ③ Nano ZnO precursor generation:
[0047] Zinc ions attach to red mud and generate basic zinc carbonate in an alkaline environment:
[0048] Zn 2+ +CO2 2- +OH - +H2O→ (ZnCO3·2Zn (OH)2·H2O) ↓
[0049] ④ Drying and calcination:
[0050] The basic zinc carbonate generated above is calcined at high temperature to obtain nano ZnO:
[0051] ZnCO3·2Zn (OH)2·H2O→ZnO+H2O↑+CO2↑
[0052] ⑤Organic treatment:
[0053] The red mud product loaded with nano ZnO was treated organically using aluminate coupling agent:
[0054] (OR')2AlOR+C2H5OH+OH - →(OR')2AlO - +C2H5OR+H2O
[0055] The preparation process of the above-mentioned nano ZnO / red mud composite modifier, the treatment process and raw materials used, and the mechanism are as follows:
[0056] (a) The core of step (1) is to purify and remove impurities from red mud. The blocky red mud is crushed into small particles by a crusher to facilitate screening. The raw material for cleaning and removing impurities is deionized water to remove impurities.
[0057] (b) The core of step (2) is the acidification treatment of red mud, in which oxalic acid reacts with some alkaline oxides in the red mud to release active hydroxyl groups. This not only increases the loading sites of nano-ZnO on the red mud, but also increases the specific surface area of the red mud to facilitate the loading of zinc oxide.
[0058] (c) The core of step (3) and step (4) is the preparation of nano ZnO precursor, and the raw materials involved include acidified red mud, zinc salt, surfactant and precipitant, wherein: red mud provides loading points for nano ZnO, zinc salt is used as the source of zinc element, the application of surfactant is aimed at improving the dispersion uniformity of precursor solution and reducing agglomeration phenomenon, and precipitant is used to promote the formation of precursor; and the preparation process involves ultrasonic treatment process, which is aimed at making the substances in the mixed solution 2 dispersed evenly;
[0059] (d) The core of step (5) is to prepare a red mud product loaded with nano ZnO, wherein: the muffle furnace provides high temperature conditions, and basic zinc carbonate is converted into nano ZnO through a calcination process;
[0060] (e) The core of step (6) is the organic treatment, in which the red mud product loaded with nano-ZnO is organically treated by using an aluminate coupling agent, wherein: the active hydroxyl groups on the surface of the red mud react with the coupling agent to convert the hydrophilicity of the product into lipophilicity, thereby improving the compatibility between the prepared nano-ZnO / red mud composite modifier and asphalt, so that the composite modifier can remain stable in the matrix asphalt.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] 1. The ZnO / red mud composite modifier in the prior art is generally directly added with finished ZnO and red mud. The red mud and finished ZnO are directly physically mixed in a certain ratio. This is a "compounding" method, that is, red mud and ZnO are directly mixed, and the obtained red mud-based composite asphalt anti-aging agent is a compound material. The nano ZnO / red mud composite modifier prepared in the present invention is a "compounding" method, using zinc acetate as a precursor solution and red mud as a carrier to generate nano ZnO in red mud, load the nano ZnO in red mud, and use chemical methods to allow the nucleation process of ZnO to occur on the red mud. The two are connected by chemical bonds, and the combination is more firm. The content of nano ZnO is characterized by X-ray fluorescence spectrometer test (XRF). The nano ZnO in the nano ZnO / red mud composite modifier prepared by the chemical loading method (hydrolysis precipitation method) adopted in the present invention is chemically bonded to the red mud. When the nano ZnO / red mud composite modifier prepared by the present invention is added to asphalt, the red mud and zinc oxide will not disperse, but will be combined together. The stability of the two in the asphalt is stronger, so that the relative uniformity of the nano ZnO and red mud in the asphalt is guaranteed, and the modification effect of the composite material in the asphalt can be better exerted. The nano ZnO / red mud composite modifier prepared by the present invention realizes the effective utilization of red mud, a solid waste, and exhibits significant environmentally friendly characteristics. This technology can not only significantly improve the environmental protection efficiency, but also successfully transform the red mud, which was originally regarded as waste, into a valuable resource, realizing the recycling of waste resources.
[0063] 2. The ZnO / red mud composite modifier in the prior art generally dissolves the coupling agent and deionized water, and adopts the "direct spraying" method for coupling treatment. The nano ZnO / red mud composite modifier prepared by the present invention uses anhydrous ethanol as a surfactant as the coupling agent, dissolves the coupling agent in anhydrous ethanol, and then adds the pre-prepared non-organized ZnO / red mud composite modifier to it, performs a chemical reaction, and completes the organic treatment (without water in the whole process), so that the ZnO / red mud composite modifier is transformed from hydrophilic to lipophilic. This treatment method can more effectively and comprehensively realize the connection between the coupling agent and the modifier, ensure that all particles of the modifier are transformed into lipophilicity, thereby enhancing the compatibility of the ZnO / red mud composite modifier with asphalt. Therefore, the components of the nano ZnO / red mud composite modifier prepared by the present invention have a synergistic effect, which can improve the modification effect: a single nano ZnO particle and a single red mud are easy to agglomerate, and when ZnO is loaded into the red mud, due to the bonding effect between ZnO and the red mud, the mutual attraction between the ZnO particles is suppressed, thereby reducing the agglomeration effect of ZnO; at the same time, ZnO occupies the hydroxyl group of the active group of the red mud, reduces the active group of the red mud, suppresses the mutual attraction between the red mud, and thus reduces the agglomeration effect of the red mud.
[0064] 3. The ZnO / red mud composite modifier in the prior art is generally not subjected to acid treatment and ultrasonic treatment, while the nano ZnO / red mud composite modifier prepared by the present invention adds an acidification treatment step and an ultrasonic treatment step, mainly considering that red mud is alkaline and directly added to asphalt will damage the asphalt performance, acid treatment can protect the performance of asphalt, and at the same time can increase the specific surface area of red mud and increase its anti-aging effect on asphalt; ultrasonic treatment can make the red mud dispersed evenly during the treatment process, so as to better react. Therefore, the nano ZnO / red mud composite modifier prepared by the present invention can further improve the thermal oxidation resistance and ultraviolet aging resistance of asphalt, thereby increasing the service life of asphalt. Red mud has large voids and specific surface area, which can extend the permeation and diffusion path of oxygen and effectively block the volatilization of light components in asphalt; Nano-ZnO has a filling effect and can replace asphalt components to slow down aging behavior. At the same time, the nano-ZnO loaded on red mud has excellent scattering and absorption capabilities for ultraviolet light, which can significantly slow down the aging effect of ultraviolet rays on asphalt. Therefore, the nano-ZnO / red mud composite modifier can effectively improve the anti-aging ability of asphalt, thereby increasing the service life of asphalt pavement.
[0065] 4. The ZnO / red mud composite modifier in the prior art is generally stirred using a shear mixer (for example, at 300 rpm), while the nano ZnO / red mud composite modifier prepared by the present invention is carried out in the form of a high-speed shearing machine + mechanical agitator. The high-speed shearing effect can reduce the particle size of the modifier, and the low-speed mechanical stirring can enhance the dispersion uniformity of the modifier in the asphalt. Therefore, the nano ZnO / red mud composite modifier prepared by the present invention can improve the anti-rutting performance of asphalt. The components of the prepared nano ZnO / red mud composite modifier have a connecting effect, and have a good anti-shear effect in the process of making modified asphalt, ensuring the integrity of the modifier structure. At the same time, compared with a single red mud modifier, the nano ZnO / red mud composite modifier has a higher specific surface area, the more light components of asphalt are adsorbed, the viscosity of the asphalt increases, the elasticity decreases, and the anti-rutting performance of the asphalt is significantly improved, thereby enhancing the road performance of the asphalt. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0067] Figure 1 The microstructure comparison diagram of the products prepared in Examples 1 to 4 of the present invention (in the figure: Figure 1 (a): The product prepared in Comparative Example 2 is a single nano ZnO modifier (abbreviated as: single ZnO); Figure 1 (b): The product prepared in Comparative Example 3 is a single red mud modifier (abbreviated as: single red mud); Figure 1 (c): The product prepared in Comparative Example 4 is single nano ZnO + single red mud modifier (abbreviated as: ZnO + red mud); Figure 1 (d): represents the product prepared in Example 1, the nano ZnO / red mud composite modifier (abbreviated as: ZnO / red mud));
[0068] Figure 2 This is a comparison chart of the rutting factors of the product prepared in Example 1 of the present invention and the products prepared in Comparative Examples 1 to 4 at 60°C (in the figure: the product prepared in Example 1 is a nano ZnO / red mud composite modifier, referred to as ZnO / red mud; the product prepared in Comparative Example 1 is asphalt without any admixture, referred to as base asphalt; the product prepared in Comparative Example 5 is a single nano ZnO modified asphalt, referred to as ZnO; the product prepared in Comparative Example 6 is a single red mud modified asphalt, referred to as red mud; the product prepared in Comparative Example 7 is a nano ZnO+red mud composite modified asphalt, referred to as ZnO+red mud);
[0069] Figure 3 This is a comparison chart of the viscosity of the product prepared in Example 1 of the present invention and the products prepared in Comparative Examples 1 to 4 at 135° C.;
[0070] Figure 4 The softening point comparison diagram of the product prepared in Example 1 of the present invention and the products prepared in Comparative Examples 1 to 4 is shown. DETAILED DESCRIPTION
[0071] The following is a detailed description of the embodiments of the present invention through specific examples. It should be understood that these specific examples are only used to illustrate and interpret the present invention, but not to limit the present invention.
[0072] In order to enhance the understanding of the present invention rather than limit the scope of use of the present invention, all quantities, percentages and other values mentioned in this application are deemed to be attached with the modifier "about" in any case. Each numerical parameter should at least be regarded as the result obtained based on the given significant figures and the standard rounding method.
[0073] Unless otherwise specified, the preparation processes used in the following examples are all common test methods used in conventional situations; the raw materials, chemical reagents, etc. used, unless otherwise specified, are all items that can be purchased through conventional commercial channels such as the market.
[0074] Embodiment 1:
[0075] A method for preparing a nano ZnO / red mud composite modifier comprises the following steps:
[0076] (1) The sintered red mud particles crushed by the crusher were added into deionized water at a mass ratio of 1:8 for washing, and then the washed red mud sample was filtered, and after filtering once, it was placed in a ventilation oven for drying, and the temperature was set to 108°C. After the red mud was dried until constant weight, it was taken out for grinding and sieving, and the sieve size was 300 meshes, so as to obtain purified and dried red mud;
[0077] (2) The purified and dried sintered red mud prepared in step (1) is added to deionized water at a mass ratio of 1:4 to form a suspension, and oxalic acid is added to the suspension at a mass ratio of red mud: oxalic acid of 5:1 to obtain a mixed solution 1, and then the obtained mixed solution 1 is placed in a constant temperature water bath for uniform stirring, the temperature is set to 70°C, the speed is set to 600r / min, and the reaction is continued for 100min. After the reaction is completed, the obtained product is filtered three times and placed in a ventilated oven for drying, the temperature is set to 108°C, the obtained product is dried until constant weight, and then taken out for grinding and sieving, the sieve size is 300 mesh, and the acidified red mud is obtained;
[0078] (3) Dissolve 65.7 g of zinc acetate in 200 mL of deionized water to form a zinc acetate solution with a concentration of 0.3 mol / L, add 5 g of the acidified red mud obtained in step (2) and 106 mL of anhydrous ethanol, respectively, to obtain a mixed solution 2; after ultrasonically treating the mixed solution 2 at a frequency of 100 Hz for 20 min, add 200 mL of a 4.5 mol / L urea solution to obtain a mixed solution 3;
[0079] (4) The mixed solution 3 in step (3) was placed in a constant temperature water bath and stirred evenly for 2 h. The temperature was set to 85°C and the rotation speed was 300 r / min. After the stirring was completed, the obtained product was filtered once and placed in a ventilated oven for drying. The temperature was set to 60°C. The obtained product was dried until constant weight and then taken out for grinding and sieving. The sieve size was 300 meshes, and the red mud product loaded with nano ZnO precursor was obtained.
[0080] (5) placing the product prepared in step (4) in a muffle furnace and calcining it for 2 h at a temperature of 350° C., and finally grinding it through a 300-mesh sieve to obtain a red mud product loaded with nano-ZnO;
[0081] (6) The red mud product loaded with nano ZnO described in step (5) is added to anhydrous ethanol, and then an aluminate coupling agent is added and stirred evenly, wherein the mass ratio of the red mud product loaded with nano ZnO, anhydrous ethanol and aluminate coupling agent is 12:60:1, and then the reaction is evenly stirred in a water bath environment for 2 hours, the temperature is set to 85°C, and the speed is 360r / min. After the time is up, the obtained product is filtered three times and placed in a ventilated oven for drying, the temperature is set to 60°C, and the obtained product is dried until constant weight, then taken out for grinding and sieving, and the sieve size is 300 mesh, so as to obtain a nano ZnO / red mud composite modifier made from solid waste, and an XRF test is performed.
[0082] result:
[0083] The field emission scanning electron microscope microstructure of a nano ZnO / red mud composite modifier prepared in this example (see Figure 1 ) Observations found that: Nano-ZnO was successfully loaded into red mud. The connection between nano-ZnO and red mud restricted the movement of nano-ZnO and reduced the agglomeration of zinc oxide. At the same time, because nano-ZnO occupied the sites of red mud active groups, the agglomeration effect of red mud was also weakened.
[0084] Embodiment 2:
[0085] A nano ZnO / red mud composite modified asphalt, the preparation materials and proportions of which are as follows: 95 parts by mass of 70# road petroleum asphalt and 5 parts by mass of a nano ZnO / red mud composite modifier; wherein: the asphalt softening point is 47.6°C, the needle penetration at 25°C is 64.1dmm, and the ductility measured at 15°C is greater than 1500mm.
[0086] The manufacturing process of the nano ZnO / red mud composite modified asphalt in Example 2 is as follows:
[0087] After heating 95 parts by mass of 70# road petroleum asphalt to a molten state at 150°C, 5 parts by mass of the nano ZnO / red mud composite modifier prepared in Example 1 were added thereto. After preliminary stirring, the mixture was placed in an oil bath and first sheared at 3000 r / min for 1 h using a high-speed shearing machine. Then, a mechanical stirrer was used to stir the mixture at 2000 r / min for 1 h to ensure that the modifier prepared above was evenly dispersed in the asphalt, and finally a nano ZnO / red mud composite modified asphalt was obtained.
[0088] Comparative Example 1:
[0089] In comparative example 1, asphalt without any admixtures is prepared by the following materials and proportions: 100 parts by mass of 70# road petroleum asphalt, wherein: the asphalt softening point is 47.6°C, the needle penetration at 25°C is 64.1dmm, and the elongation measured at 15°C is greater than 1500mm.
[0090] The asphalt without any admixture in Comparative Example 1 has the following production process:
[0091] 100 parts by mass of 70# road petroleum asphalt were heated to a molten state at 150°C and then placed in an oil bath. A high-speed shearing machine was used to shear the asphalt at a speed of 3000 r / min for 1 hour. A mechanical stirrer was then used to stir the asphalt at a speed of 2000 r / min for 1 hour to ensure that the prepared modifier was evenly stirred in the asphalt. Finally, asphalt without any admixtures was obtained.
[0092] Comparative Example 2:
[0093] A method for preparing a single nano ZnO modifier comprises the following steps:
[0094] (1) Dissolve 65.7 g of zinc acetate in 200 mL of deionized water to form a zinc acetate solution with a concentration of 0.3 mol / L, add 106 mL of anhydrous ethanol to obtain a mixed solution 1; after ultrasonically treating the mixed solution 1 at a frequency of 100 Hz for 20 min, add 200 mL of a 4.5 mol / L urea solution to obtain a mixed solution 2;
[0095] (2) The mixed solution 2 in step (1) is placed in a constant temperature water bath and stirred evenly for 2 h. The temperature is set to 85°C and the rotation speed is 300 r / min. After the stirring is completed, the obtained product is filtered once and placed in a ventilation oven for drying. The temperature is set to 60°C. The obtained product is dried until constant weight is obtained and then taken out for grinding and sieving. The sieve size is 300 meshes, and a single nano ZnO precursor product is obtained.
[0096] (3) placing the product prepared in step (2) in a muffle furnace and calcining it for 2 h at a temperature of 350 °C, and finally grinding it through a 300-mesh sieve to obtain a single nano ZnO product without organic modification;
[0097] (4) The single non-organized nano ZnO product obtained in step (3) is added to anhydrous ethanol, and then an aluminate coupling agent is added and stirred evenly, wherein the mass ratio of the non-organized single nano ZnO product, anhydrous ethanol and aluminate coupling agent is 12:60:1, and then stirred evenly in a water bath environment for 2 h, the temperature is set to 85 ° C, the speed is 360 r / min, and after the time is up, the obtained product is filtered three times and placed in a ventilated oven for drying, the temperature is set to 60 ° C, the obtained product is dried until constant weight, and then taken out for grinding and sieving, the sieve size is 300 mesh, to obtain an organic single nano ZnO product, that is, a single nano ZnO modifier.
[0098] result:
[0099] Figure 1 The microstructure comparison diagram of the products prepared in Examples 1 to 4;
[0100] Field emission scanning electron microscope microscopic morphology of a single nano ZnO modifier prepared in Example 1 (see Figure 1 ) Observations found that: the agglomeration of single nano ZnO particles is obvious, and the increase in ZnO particle size will have an adverse effect on its modification effect.
[0101] Comparative Example 3:
[0102] A method for preparing a single red mud modifier comprises the following steps:
[0103] (1) The sintered red mud particles crushed by the crusher were added into deionized water at a mass ratio of 1:8 for washing, and then the washed red mud sample was filtered, and after filtering once, it was placed in a ventilation oven for drying, and the temperature was set to 108°C. After the red mud was dried until constant weight, it was taken out for grinding and sieving, and the sieve size was 300 meshes, so as to obtain purified and dried red mud;
[0104] (2) The purified and dried sintered red mud prepared in step (1) is added to deionized water at a mass ratio of 1:4 to form a suspension, and oxalic acid is added to the suspension at a mass ratio of red mud: oxalic acid of 5:1 to obtain a mixed solution 1, and then the obtained mixed solution 1 is placed in a constant temperature water bath for uniform stirring, the temperature is set to 70°C, the speed is set to 600 r / min, and the reaction is continued for 100 min. After the reaction is completed, the obtained product is filtered three times and placed in a ventilated oven for drying, the temperature is set to 108°C, the obtained product is dried until constant weight, and then taken out for grinding and sieving, the sieve size is 300 mesh, and the acidified red mud is obtained;
[0105] (3) Take 200 mL of deionized water, add 5 g of the acidified red mud obtained in step (2) and 106 mL of anhydrous ethanol respectively, to obtain a mixed solution 2; after ultrasonically treating the mixed solution 2 at a frequency of 100 Hz for 20 min, add 200 mL of a 4.5 mol / L urea solution, to obtain a mixed solution 3;
[0106] (4) The mixed solution 3 in step (3) is placed in a constant temperature water bath and stirred evenly for 2 h. The temperature is set to 85°C and the rotation speed is 300 r / min. After the stirring is completed, the obtained product is filtered once and placed in a ventilated oven for drying. The temperature is set to 60°C. The obtained product is dried until constant weight and then taken out for grinding and sieving. The sieve size is 300 mesh. The prepared product is placed in a muffle furnace and calcined for 2 h. The temperature is set to 350°C. Finally, it is ground through a 300-mesh sieve, i.e., a single red mud product without organicization;
[0107] (5) The unorganized single red mud product of step (4) is added to anhydrous ethanol, and then an aluminate coupling agent is added and stirred evenly, wherein the mass ratio of the unorganized single red mud product, anhydrous ethanol and aluminate coupling agent is 12:60:1, and then stirred evenly in a water bath environment for 2 h, the temperature is set to 85 ° C, the speed is 360 r / min, and after the time is up, the obtained product is filtered three times and placed in a ventilated oven for drying, the temperature is set to 60 ° C, the obtained product is dried until constant weight, and then taken out for grinding and sieving, the sieve size is 300 mesh, to obtain an organized single red mud product, i.e., a single red mud modifier.
[0108] result:
[0109] The field emission scanning electron microscope microstructure of a single red mud modifier prepared in this example (see Figure 1 ) Observations found that: the surface of a single red mud has many gaps and a large specific surface area, which can adsorb asphalt into the gaps, thereby inhibiting or delaying the entry of oxygen, and has the potential to enhance the anti-aging properties of asphalt.
[0110] Comparative Example 4:
[0111] A method for preparing a nano ZnO+red mud composite modifier comprises the following steps:
[0112] The single nano-ZnO product after organization described in the above comparative example 3 and the single red mud product after organization described in comparative example 4 were physically blended at a mass ratio of 61.6:38.4 to prepare a single nano-ZnO+single red mud physical blending modifier product, i.e., a nano-ZnO+red mud composite modifier.
[0113] result:
[0114] The field emission scanning electron microscope microstructure of the nano ZnO + red mud composite modifier prepared in this example (see Figure 1 ) Observations found that single nano-ZnO and red mud were unevenly distributed, with nano-ZnO concentrated in the middle of the image and accompanied by agglomeration; while red mud was mainly distributed on both sides of the image, indicating that simple physical blending could not load nano-ZnO into red mud and reduce the occurrence of agglomeration effect.
[0115] Comparative Example 5:
[0116] The single nano-ZnO modified asphalt in Comparative Example 5 has the following preparation materials and proportions: 96.9 parts by mass of 70# road petroleum asphalt and 3.1 parts by mass of a single nano-ZnO modifier; wherein: the asphalt softening point is 47.6°C, the needle penetration at 25°C is 64.1 dmm, and the elongation measured at 15°C is greater than 1500 mm.
[0117] The manufacturing process of a single nano ZnO modified asphalt in Comparative Example 5 is as follows:
[0118] 96.9 parts by mass of 70# road petroleum asphalt were heated to a molten state at 150°C, and 3.1 parts by mass of the single nano ZnO modifier prepared in Comparative Example 2 were added thereto. After preliminary stirring, the asphalt was placed in an oil bath and first sheared at 3000 r / min for 1 h using a high-speed shearing machine. Then, a mechanical stirrer was used to stir the asphalt at 2000 r / min for 1 h to ensure that the modifier prepared above was evenly dispersed in the asphalt, and finally a single nano ZnO modified asphalt was obtained.
[0119] Comparative Example 6:
[0120] The single red mud modified asphalt in Comparative Example 6 has the following preparation materials and proportions: 98.1 parts by mass of 70# road petroleum asphalt and 1.9 parts by mass of a single red mud modifier; wherein: the asphalt softening point is 47.6°C, the needle penetration at 25°C is 64.1 dmm, and the elongation measured at 15°C is greater than 1500 mm.
[0121] The production process of a single red mud modified asphalt in Comparative Example 6 is as follows:
[0122] 98.1 parts by mass of 70# road petroleum asphalt were heated to a molten state at 150°C, and 1.9 parts by mass of the single red mud modifier prepared in Comparative Example 3 were added thereto. After preliminary stirring, the asphalt was placed in an oil bath and first sheared at 3000 r / min for 1 h using a high-speed shearing machine. Then, a mechanical stirrer was used to stir the asphalt at 2000 r / min for 1 h to ensure that the modifier prepared above was evenly dispersed in the asphalt, and finally a single red mud modified asphalt was obtained.
[0123] Comparative Example 7:
[0124] The nano-ZnO+red mud composite modified asphalt in Comparative Example 7 has the following preparation materials and proportions: 95 parts by mass of 70# road petroleum asphalt, 3.1 parts by mass of a single nano-ZnO modifier, and 1.9 parts by mass of a single red mud modifier; wherein: the asphalt softening point is 47.6°C, the needle penetration at 25°C is 64.1 dmm, and the elongation measured at 15°C is greater than 1500 mm.
[0125] The manufacturing process of the nano ZnO+red mud compound modified asphalt in Comparative Example 7 is as follows:
[0126] 95 parts by mass of 70# road petroleum asphalt were heated to a molten state at 150°C, and 5 parts by mass of the nano ZnO + red mud composite modifier prepared in Comparative Example 4 were added thereto. After preliminary stirring, the mixture was placed in an oil bath and first sheared at 3000 r / min for 1 h using a high-speed shearing machine. Then, a mechanical stirrer was used to stir the mixture at 2000 r / min for 1 h to ensure that the modifier prepared above was evenly dispersed in the asphalt, and finally the nano ZnO + red mud composite modified asphalt was obtained.
[0127] Performance Testing:
[0128] According to T0628-2011 of "JTG E20-2011 Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (hereinafter referred to as "Test Procedure"), the asphalt rheological property test was carried out, and the rutting factor corresponding to 60°C in the temperature scanning test was used to analyze the nano ZnO / red mud composite modified asphalt prepared in Example 2. Figure 2 The results show that the rutting factor of the single red mud modified asphalt prepared in Comparative Example 6 is the smallest, which is 3195.2 Pa; the rutting factor of the nano-ZnO / red mud composite modified asphalt prepared in Example 2 is the largest, which is 3707.5Pa, which is 462 Pa higher than the rutting factor of 3244.7Pa of the asphalt without any admixture prepared in Comparative Example 1; and it is 370.6 Pa higher than the rutting factor of 3336.9Pa of the nano-ZnO+red mud composite modified asphalt prepared in Comparative Example 7.
[0129] Figure 2 It is a comparison chart of the rutting factors of the product prepared in Example 1 and the products prepared in Comparative Examples 1 to 4 at 60°C;
[0130] In addition, the rotational viscosity at 135°C after short-term aging, long-term aging and UV aging of the nano ZnO / red mud composite modified asphalt prepared in Example 2, the asphalt without any admixture prepared in Comparative Example 1, the single nano ZnO modified asphalt prepared in Comparative Example 5, the single red mud modified asphalt prepared in Comparative Example 6 and the nano ZnO+red mud composite modified asphalt prepared in Comparative Example 7 were measured with reference to T 0625-2011 in the Test Procedure and T 0606-2011 in the Test Procedure. Figure 3 ) and softening point (see Figure 4 ) was measured, of which short-term aging was carried out according to the thin film oven (TFOT) aging test in T 0609-2011 of the Test Procedure, long-term aging was simulated by aging at 163°C in a thin film oven for 20h, and UV aging was simulated by a self-made UV aging box (aging temperature: 60°C; UV radiation intensity: 8W / m 2 ; Aging time: 12 days). The test results are as follows:
[0131] The viscosity of the asphalt without any admixture prepared in Comparative Example 1 increased from 490.6 Pa to 596.3 Pa before and after short-term aging (see Figure 3 ), increased by 105.7Pa, the largest increase, and its softening point increased from 47.6℃ to 50.9℃ before and after short-term aging (see Figure 4 ), increased by 3.3 ° C, indicating that the short-term aging of this modified asphalt is the most serious; while the viscosity of the nano ZnO / red mud composite modified asphalt prepared in Example 2 increased from 559.4 Pa to 631.3 Pa before and after short-term aging (see Figure 3 ), increased by 71.9Pa, which is the smallest increase compared with other modified asphalt products. At the same time, its softening point increased from 49.9℃ to 51.3℃ before and after short-term aging (see Figure 4 ), increased by 1.4°C, which is the smallest increase compared to other modified asphalt products, indicating that the nano ZnO / red mud composite modified asphalt prepared in Example 2 has the best anti-short-term aging performance;
[0132] The viscosity of the asphalt without any admixture prepared in Comparative Example 1 increased from 490.6 Pa to 1409 Pa before and after long-term aging (see Figure 3 ), increased by 812.7Pa, the largest increase, and its softening point increased from 47.6℃ to 61.1℃ before and after long-term aging (see Figure 4), increased by 10.2 ° C, indicating that the long-term aging of this modified asphalt is the most serious; while the viscosity of the nano ZnO / red mud composite modified asphalt prepared in Example 2 increased from 559.4 Pa to 1313 Pa before and after long-term aging (see Figure 3 ), increased by 681.7Pa, which is the smallest increase compared with other modified asphalt products. At the same time, its softening point increased from 49.9℃ to 60.4℃ before and after long-term aging (see Figure 4 ), increased by 9.1°C, which is the smallest increase compared to other modified asphalt products, indicating that the nano ZnO / red mud composite modified asphalt prepared in Example 2 has the best long-term aging resistance;
[0133] The viscosity of the asphalt without any admixture prepared in Comparative Example 1 increased from 490.6 Pa to 795.2 Pa before and after UV aging (see Figure 3 ), increased by 304.6Pa, the largest increase, and its softening point increased from 47.6℃ to 54.7℃ before and after UV aging (see Figure 4 ), increased by 7.1 ° C, indicating that the modified asphalt is most severely UV-aged; while the viscosity of the nano ZnO / red mud composite modified asphalt prepared in Example 2 increased from 559.4 Pa to 689.3 Pa before and after UV aging (see Figure 3 ), increased by 129.9Pa, which is the smallest increase compared with other modified asphalt products. At the same time, its softening point increased from 49.9℃ to 53.6℃ before and after UV aging (see Figure 4 ), increased by 3.7°C, which is the smallest increase compared to other modified asphalt products, indicating that the nano ZnO / red mud composite modified asphalt prepared in Example 2 has the best anti-ultraviolet aging performance;
[0134] Figure 3 This is a comparison chart of the viscosity of the product prepared in Example 1 of the present invention and the products prepared in Comparative Examples 1 to 4 at 135° C.;
[0135] Figure 4 The softening point comparison diagram of the product prepared in Example 1 of the present invention and the products prepared in Comparative Examples 1 to 4 is shown.
[0136] Summary and discussion:
[0137] The present invention adopts a hydrolysis precipitation method to successfully load nano ZnO onto red mud, and then prepares a new type of nano ZnO / red mud composite modifier. By comparing with a single nano ZnO modifier, a single red mud modifier, and a nano ZnO+red mud composite modifier, it is determined that the synergistic effect between the components of the new nano ZnO / red mud composite modifier can enhance the connection effect between nano ZnO and red mud, restrict the free movement of nano ZnO, and thus reduce the agglomeration effect between nano ZnO and red mud; after organic treatment, the compatibility of the nano ZnO / red mud composite modifier with asphalt is improved, which promotes the uniform distribution of the nano ZnO / red mud composite modifier in the asphalt, and the modification effect is guaranteed; the addition of the nano ZnO / red mud composite modifier enables the asphalt to have a better heat-oxidative aging resistance effect, and also significantly improves the light-oxidative aging resistance of the asphalt, which can effectively reduce road surface diseases and extend the service life of the asphalt pavement. This is of great significance for solid waste treatment, improvement of asphalt road performance and saving of pavement investment costs.
[0138] In summary, it can be concluded from the above that the synergistic effect between the components of a nano ZnO / red mud composite modifier prepared using solid waste can improve the bonding strength between nano ZnO and red mud and reduce agglomeration; when added to asphalt, the resulting nano ZnO / red mud composite modified asphalt has better resistance to thermal oxygen aging and ultraviolet aging, and can also enhance the anti-rutting performance of asphalt and improve the service life of asphalt pavement.
[0139] The preferred embodiments of the present invention are described in detail above in combination with the embodiments and comparative examples. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical scheme of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0140] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0141] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a nano ZnO / red mud composite modifier made from solid waste, characterized in that: The following steps are involved: (1) The red mud recovered from the factory is crushed by a crusher, washed with deionized water, and then the obtained sample is filtered and dried to constant weight, followed by sieving to obtain purified and dried red mud; The red mud is sintered red mud, Bayer red mud, or combined process red mud; (2) dispersing the purified and dried red mud in step (1) in deionized water in a mass ratio of 1:4 between the purified and dried red mud and the deionized water, stirring to form a suspension, adding oxalic acid to the suspension in a mass ratio of 5:1 between the purified and dried red mud and the oxalic acid, and obtaining a mixed solution 1; Then the obtained mixed solution 1 was placed in a constant temperature water bath and stirred evenly for 100 min, the speed was 600 r / min, the temperature was set to 70 °C, and the pH was tested to be 6-8. After the reaction was completed, the obtained product was filtered, dried to constant weight, and finally ground and sieved to obtain acidified red mud. (3) dissolving zinc salt in deionized water to form a zinc salt solution with a concentration of 0.3 mol / L; adding the acidified red mud obtained in step (2) and a surfactant to the zinc salt solution according to a ratio to obtain a mixed solution 2, wherein the ratio of zinc ions to acidified red mud is 60 mmol / g, and the molar ratio of zinc ions to surfactant is 1:6; subjecting the mixed solution 2 to ultrasonic treatment for 20 min at a frequency of 100 Hz, and then adding a precipitant to obtain a mixed solution 3, wherein the molar ratio of the precipitant to zinc ions is 3:1; The zinc salt is zinc acetate and is analytically pure; The surfactant is anhydrous ethanol; The precipitant is urea of analytical grade; (4) The mixed solution 3 in step (3) was placed in a constant temperature water bath and stirred evenly for 2 h at a speed of 300 r / min and a temperature of 85 °C. After the stirring was completed, the mixed solution was filtered and dried to a constant weight to obtain a red mud product loaded with nano-ZnO precursor; (5) The red mud product loaded with nano ZnO precursor obtained in step (4) is placed in a muffle furnace and calcined for 2 h at a temperature of 350 °C, and finally ground and sieved to obtain a red mud product loaded with nano ZnO; (6) The red mud product loaded with nano-ZnO obtained in step (5) is dispersed in anhydrous ethanol, wherein the mass ratio of the red mud product loaded with nano-ZnO to the anhydrous ethanol is 1:5; an organic coupling agent is added, wherein the mass ratio of the red mud product loaded with nano-ZnO to the organic coupling agent is 12:1, and the organic coupling agent is an aluminate coupling agent or a titanate coupling agent; the mixture is stirred uniformly in a water bath for 2 h, the speed is 360 r / min, and the temperature is set to 85°C. After the reaction is completed, the mixture is filtered, dried to constant weight, and finally ground and sieved to obtain a nano-ZnO / red mud composite modifier made from solid waste; the nano-ZnO / red mud composite modifier made from solid waste has the following performance parameters: ①With 23.574 m 2 / g specific surface area and nanoscale pore size, pore volume of 0.11 cc / g, and average pore size of 3.742nm; ②Through XRF testing, the proportion of ZnO in the nano ZnO / red mud composite modifier is 61.6%-63.0%.
2. The method for preparing a nano ZnO / red mud composite modifier made from solid waste according to claim 1, characterized in that: In step (1), the red mud is washed with deionized water in a mass ratio of 1:8 between crushed red mud and deionized water; the red mud is sintered red mud; the sample is dried in a ventilated oven at a temperature of 108°C; the filtration is performed once; and the sieving is performed with a sieve hole size of 300 mesh.
3. The method for preparing a nano ZnO / red mud composite modifier made from solid waste according to claim 1, characterized in that: The filtration in step (2) is performed three times; the drying is performed in a ventilated oven at a drying temperature of 108°C; and the sieving is performed with a sieve size of 300 mesh.
4. The method for preparing a nano ZnO / red mud composite modifier made from solid waste according to claim 1, characterized in that: The number of filtrations in step (4) is one time; the drying is carried out in a ventilated oven at a drying temperature of 60°C.
5. The method for preparing a nano ZnO / red mud composite modifier made from solid waste according to claim 1, characterized in that: The sieving in step (5) has a sieve size of 300 mesh.
6. The method for preparing a nano ZnO / red mud composite modifier made from solid waste according to claim 1, characterized in that: The drying described in step (6) is to place the sample in a ventilated oven for drying at a temperature of 60° C. The sieving is performed with a sieve size of 300 mesh.
7. A nano ZnO / red mud composite modifier made from solid waste, characterized in that: The nano ZnO / red mud composite modifier prepared by using solid waste is obtained by using the preparation method of any one of claims 1 to 6. The nano ZnO / red mud composite modifier prepared by using solid waste has the following performance parameters: ①With 23.574 m 2 / g specific surface area and nanoscale pore size, pore volume of 0.11 cc / g, and average pore size of 3.742nm; ②Through XRF testing, the proportion of ZnO in the nano ZnO / red mud composite modifier is 61.6%-63.0%.
8. The use of a nano ZnO / red mud composite modifier made from solid waste as claimed in claim 7, characterized in that: The method for preparing ZnO / red mud composite modified asphalt comprises the following steps: (1) Prepare the following raw materials in the following mass proportions: 100 parts by mass of modified asphalt, including 95 parts by mass of 70# road petroleum asphalt and 5 parts by mass of nano ZnO / red mud composite modifier; (2) After heating 95 parts by mass of asphalt at 150°C to a molten state, 5 parts by mass of the nano ZnO / red mud composite modifier was added thereto. After preliminary stirring, it was placed in an oil bath and first sheared at 3000 r / min for 1 h using a high-speed shearing machine. Then, a mechanical stirrer was used to stir at 2000 r / min for 1 h to ensure that the modifier prepared above was evenly dispersed in the asphalt, and finally the nano ZnO / red mud composite modified asphalt was obtained.
9. The use of a nano ZnO / red mud composite modifier made from solid waste according to claim 8, characterized in that: The 70# road petroleum asphalt described in step (1) has a softening point of 47.6°C, a needle penetration of 64 dmm to 65 dmm at 25°C, and an elongation of >1500 mm at 15°C.
Citation Information
Patent Citations
Inorganic pigment or filler surface treatment with amine-imide - gives ready dispersibility in water and organic media
CH587327A5
Process for preparing enhanced neutral spherical ozone catalyst from red mud
CN114345354A